Strengthening Student Competence Through Cyber-Based Integrative Islamic Education Learning Design: A Review of Islamic Sociology - Hosaini, Hosaini; Waziroh, Iro; Minhaji, Minhaji; Alehirish, Mustafa Hamed Mohamed (Indonesian Journal Publisher in cooperation with Indonesian Social Studies Association (APRIPSI), 2025)
This research is motivated by the need for Islamic boarding schools (pesantren) to adapt to the development of information technology without losing the distinctive character of Islamic education. As one of the largest Islamic boarding schools in Indonesia, Sukorejo Islamic Boarding School is faced with the challenge of strengthening the competency of its students so they can face global dynamics while remaining grounded in Islamic values. This study aims to formulate and analyze a cyber-based integrative learning design that can improve students' overall competency through an Islamic sociological approach. The methodology used is a qualitative and phenomenological, through field observations and in-depth interviews with teachers, students, and Islamic boarding school administrators. The results show that the implementation of the cyber-based integrative learning design has a significant impact on improving the competency of students, both in cognitive aspects (Islamic knowledge), affective (strengthening morals and spirituality), and social (the ability to interact in the digital space). The study of Islamic sociology confirms that this learning innovation can maintain the continuity of tradition and modernity in a single value, strengthening the identity of the Islamic boarding school as an agent of Islamic-based social transformation.